2014
DOI: 10.1111/tbed.12254
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes and Beliefs of Pig Farmers and Wild Boar Hunters Towards Reporting of African Swine Fever in Bulgaria, Germany and the Western Part of the Russian Federation

Abstract: SummaryThis study investigated the attitudes and beliefs of pig farmers and hunters in Germany, Bulgaria and the western part of the Russian Federation towards reporting suspected cases of African swine fever (ASF). Data was collected using a web-based questionnaire survey targeting pig farmers and hunters in these three study areas. Separate multivariable logistic regression models identified key variables associated with each of the three binary outcome variables whether or not farmers would immediately repo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
37
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 42 publications
(38 citation statements)
references
References 20 publications
0
37
0
1
Order By: Relevance
“…A study carried out in Great Britain showed that English pig farmers had poor knowledge about ASF as well as limited concern about it (26). Vergne et al (102) also highlighted that the reasons for lack of immediate reporting in suspected ASF cases in Germany, the Russian Federation, and Bulgaria would be due to not knowing reporting procedures, fear that the report could have a negative impact on their reputation, and assuming they would be capable of handling the outbreak on their own. These studies (26, 102, 103) suggested that there is still room for improving farmers’ knowledge to bridge the gap between authorities and farmers and consequently help prevent the spread of ASF (39).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A study carried out in Great Britain showed that English pig farmers had poor knowledge about ASF as well as limited concern about it (26). Vergne et al (102) also highlighted that the reasons for lack of immediate reporting in suspected ASF cases in Germany, the Russian Federation, and Bulgaria would be due to not knowing reporting procedures, fear that the report could have a negative impact on their reputation, and assuming they would be capable of handling the outbreak on their own. These studies (26, 102, 103) suggested that there is still room for improving farmers’ knowledge to bridge the gap between authorities and farmers and consequently help prevent the spread of ASF (39).…”
Section: Discussionmentioning
confidence: 99%
“…Vergne et al (102) also highlighted that the reasons for lack of immediate reporting in suspected ASF cases in Germany, the Russian Federation, and Bulgaria would be due to not knowing reporting procedures, fear that the report could have a negative impact on their reputation, and assuming they would be capable of handling the outbreak on their own. These studies (26, 102, 103) suggested that there is still room for improving farmers’ knowledge to bridge the gap between authorities and farmers and consequently help prevent the spread of ASF (39). Similarly, to be able to effectively influence farm workers, veterinarians, and hunters’ behavior, it is essential to analyze the “at-risk” practices that depended on human behavior which can perpetuate ASF spread and find out measures tailored to each specific situation.…”
Section: Discussionmentioning
confidence: 99%
“…There are many factors that may have influenced the difference in seasonality of cases in wild boars in the Russian Federation. These factors have been linked to ecology of wild boar, timing of spillovers from domestic pigs (EFSA, ) and could also be related to wild boar surveillance although the likelihood of reporting wild boar carcasses and harvested wild boar was low in the western part of the RF as many hunters are unaware of the possibility to report (Vergne et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, the surveillance data are very likely to represent only a subset of all the outbreaks that occurred in the two regions. In addition, the reporting bias is likely to have varied in space and time as a result of the diversity of human behaviours associated with reporting of ASF suspicions (Vergne et al., ). Spatial and temporal heterogeneity of the under‐reporting rate are known to potentially decrease the statistical power of the space‐time K ‐function.…”
Section: Discussionmentioning
confidence: 99%